A STUDY OF EUPHEMIZED ABUSIVE JAVANESE TERMS AND THEIR FIGURATIVE MEANINGS - Yoseph Edmundus Budiyana; Rakhmadati Dagsani (Soegijapranata Catholic University, 2013)
Speech community frequently uses language for insulting. This study deals with a perspective to find out the classification of the euphemized abusive Javanese terms based on Huang and Warren (1993) and their figurative meanings. By using qualitative method, the writer collected nine public documents related to the euphemized abusive Javanese terms. Then, they were examined and validated by five Javanese experts such as lecturers, puppeteers, and teachers to check their accuracy. The results show that based on Huang and Warrens theory, abstract and spirit provenance for insult attacking physical shortcomings; intellectual shortcomings; character and personality deviations; and personal behavior and social deviations are absent. Secondly, the euphemized abusive Javanese terms for insult attacking physical shortcomings are not found. Thirdly, new provenance, emotion is found in insult attacking characters and personalities. Lastly, from figurative meaning facet, the majority of the euphemized abusive Javanese terms have metaphorical meanings, while the others belong to irony and simile.